2015
DOI: 10.1177/1071100715586182
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Insertional Achilles Tendinopathy With or Without Flexor Hallucis Longus Tendon Transfer

Abstract: Level 1, prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 23 publications
1
63
0
2
Order By: Relevance
“…50 Complications resulting from this procedure have ranged from 6 to over 30 percent in the literature and are most commonly due to wound healing issues, painful scar, or sural nerve injury. 32,42,43,49,67,68 …”
Section: Operative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Complications resulting from this procedure have ranged from 6 to over 30 percent in the literature and are most commonly due to wound healing issues, painful scar, or sural nerve injury. 32,42,43,49,67,68 …”
Section: Operative Treatmentmentioning
confidence: 99%
“…49 Eighteen patients in the control group underwent Achilles decompression and debridement and 19 patients in the FHL transfer group underwent decompression and debridement along with FHL augmentation for chronic IAT. The 2 groups demonstrated no differences in pain, functional outcomes, or patient satisfaction.…”
Section: Operative Treatmentmentioning
confidence: 99%
“…This is frequent in patients aged over 50 years. However, a recent randomised trial showed no difference between two groups of patients who underwent decompression and debridement, with or without FHL tendon transfer 20. A relevant complication of this surgery is the accidental resection of the medial or lateral plantar nerve 59.…”
Section: Management Of Iatmentioning
confidence: 99%
“…Very good ankle plantar exion strength and an overall clinical success rate of over 70% have been reported. (27)(28)(29) As such, the management for Achilles tendinopathy experiences a variety of treatment strategies and lacks standardized criteria as it depends on subjective considerations of the caretaker. (30) The observed FHL hypertrophy in patients with signs of chronic Achilles tendinopathy provides evidence that further supports its functional synergism and as such, another argument for choosing an FHL transfer.…”
Section: Discussionmentioning
confidence: 99%